Ethnic differences in the risk of caesarean section: a Danish population-based register study 2004-2015 - Trine Damsted Rasmussen; Sarah Fredsted Villadsen; Per Kragh Andersen; Tine Dalsgaard Clausen; Anne-Marie Nybo Andersen (BMC, 2019)
Abstract Background Studies have shown differences in the risk of caesarean section (CS) between ethnic minority groups. This could be a marker of unequal health care. The aim of this study was to investigate differences in the risk of CS between immigrants of various origins in Denmark, where all health care is free and easy to access, and Danish-born women. A further aim was to determine the possible influence of known risk factors for CS. Methods The design was a population-based register study using national Danish registers and included all live- and stillborn singleton deliveries by primiparous women in Denmark from 2004 to 2015. The total study population consisted of 298,086 births, including 25,198 births to women from the 19 largest immigrant groups in Denmark. Multinomial logistic regression analysis was used to estimate relative risk ratios (RRR) of emergency and planned CS, using vaginal delivery (VD) as reference, in immigrant women compared to Danish-born women. A number of known risk factors were included separately. Results Women from Turkey, the Philippines, Thailand, Somalia, Vietnam, Iran and Afghanistan had a statistically significant elevated risk ratio of emergency CS vs. VD compared to Danish-born women; adjusted RRR's ranging 1.15-2.19. The risk ratio of planned CS vs. VD was lower among the majority of immigrant groups, however higher among women from Poland, Thailand and Iran, when compared to Danish-born women. None of the studied explanatory variables affected the risk ratio of planned CS vs. VD, whereas maternal height contributed with varying strength to the risk ratio of emergency CS vs. VD for all immigrant groups. Conclusion Substantial variations in CS risks by maternal country of birth were documented. Some of the disparities in emergency CS seem to be explained by maternal height.